Air untuk Semua: Tantangan Kebijakan Sosial pada Distribusi Air di Komunitas Lokal - Rifandini, Rahmalia (UI Scholars Hub, 2024)
Water is a non-economic good that undoubtedly plays an important role in improving people's well-being. Global data shows that the agricultural sector is the most water- consuming base of life, especially for local communities that rely on agriculture. Increasing food production in the future along with population growth will potentially demand sustainable water resource management. Water regulation plays an important role in determining the allocation, distribution and use of water resources. Lack of availability and access to water creates mutual vulnerability among environmental and social ecosystems. The legitimacy crisis of water governance is a major issue faced by lower-level bureaucracies (Turley, 2021). Previous studies attribute the functioning of democracy at the local level to contribute to water governance (Fawcett and Marsh, 2013; Harmes, 2021). However, social policies on water have not been considered as part of basic services from the main focus of classical traditional policies. This article discusses the importance of social policies for water that illustrate the relationship between people's well-being and water availability and the challenges faced at the local community level. Adequate water management contributes to an indicator of well-being. The implementation of social policy on water distribution is a complex issue and raises fundamental questions related to availability and accessibility.